By the balls : the complete - Fassbender, Tom (Akashic Books, 2013)
REINTRODUCING HARD-BOILED DETECTIVE BEN DRAKE to a whole new generation, By the Balls: The Complete Collection assembles all the early writing of Jim Pascoe and Tom Fassbender--including the bowling alley murder mystery that launched crime fiction house UglyTown--in a redesigned 15th anniversary edition. This deluxe package contains the two underground cult-classic novels By the Balls and Five Shots and a Funeral, along with two brand-new short stories, a new introduction, illustrations by Paul Pope, and over a dozen short essays by industry luminaries. PERFECT FOR FANS OF HAMMETT AND CHANDLER, these tales follow the exploits of Ben Drake, a detective with a passion for small cigars and big fights, a love of Old Grand-Dad, and a weakness for women in trouble. North of Las Vegas in the fictional town of Testacy City, Drake sniffs out killers, thieves, kidnappers, cock fighters, double crossers, crooked cops, and numbers runners--all culminating in the bizarre murder of Gentleman Joe Biggs, a well-loved local bowling hero. As he continues to crack clues in the case, Drake is drawn deeper into a citywide criminal conspiracy.